KOSMOS 2020 Peru mesocosm on ecosystem responses to different light and upwelling intensities: zooplankton dynamics via Plankton Imaging with Scanning Optics (PIScO) - Dausmann, Veit; Theileis, Anton; Goldenberg, Silvan Urs; Taucher, Jan (PANGAEA, 2025)
Zooplankton dynamics during the mesocosm experiment in the Peruvian upwelling system near Lima from February-April 2020. Light (ambient = high vs. reduced = low) was manipulated from the beginning (day 0) and upwelling (0 to 60% deep water addition) two weeks into the experiment (day 13). Copepods >200 µm were sampled every two days using Plankton Imaging with Scanning Optics (PIScO) (Taucher et al. 2022). This camera system was lowered from the surface to the sediment trap, scanning at three frames per second. Each image sampled 0.577 L of seawater, summing to 99 L per camera cast. Images were analyzed for copepods with an object detection algorithm trained by a human observer on 11,269 images (73% for both precision and recall). For each image, abundance and individual size (equivalent spherical diameter, ESD) was calculated. The data shown here represent averages across the entire water column, ranging from 1.15 to 10.5 m depth. Methodological details in Goldenberg et al. and Thielecke et al. (manuscripts in progress).
Keywords: mesocosm experiment